2012
DOI: 10.1007/s12034-012-0293-7
|View full text |Cite
|
Sign up to set email alerts
|

Property change during nanosecond pulse laser annealing of amorphous NiTi thin film

Abstract: Nanosecond lasers of different intensities were pulsed into sputter-deposited amorphous thin films of near equiatomic Ni/Ti composition to produce partially crystallized highly sensitive R-phase spots surrounded by amorphous regions. Scanning electron microscopy having secondary and back-scattered electrons, field emission scanning electron microscopy, optical microscopy and X-ray diffraction patterns were used to characterize the laser treated spots. Effect of nanosecond pulse lasering on microstructure, morp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Temperature rise alters functional features of Nitinol [29]. Favorable behaviors of the alloy depend on the exact composition of the mono-phase, as illustrated in Figure 2 [62,63]. Fabrication method and thermomechanical treatments influence on these features [53-55, 63, 64].…”
Section: Manufacturing Techniques Of Porous Nitinol Alloymentioning
confidence: 99%
“…Temperature rise alters functional features of Nitinol [29]. Favorable behaviors of the alloy depend on the exact composition of the mono-phase, as illustrated in Figure 2 [62,63]. Fabrication method and thermomechanical treatments influence on these features [53-55, 63, 64].…”
Section: Manufacturing Techniques Of Porous Nitinol Alloymentioning
confidence: 99%
“…Compared to these traditional annealing techniques, laser annealing has advantages including faster actuation response, rapidly cooling rate and controllable penetration depth into the substrate. It is beneficial for a uniform concentration, lower defect density and local heating area [24]. Cheng [25] reported that laser treatment results in an effective improvement in the c-axis preferred orientation of ZnO films and is thus beneficial in reducing the return loss of ZnO-based longitudinal mode FBARs.…”
Section: Introductionmentioning
confidence: 99%